Prevalence of multiple nutritional deficiencies among the street children of Khammam City of Telangana State - Berad, Aditya Suryabhan; BP, Ravi Kumar; Momula, Sampat (International Journal of Research in Medical Sciences, 2017)
Background: To study the nutritional status of the street children in Khammam city. Methods: Type of study: A prospective and descriptive study. Study Population: All the street children in the city who are less than 18 years of age. 3 Sample size: out of total 384 street children in the city, 250 were included in the study. Selection criteria: Children in different age groups of both sexes were selected. Data regarding nutritional and health status was collected by using pretested structured questionnaire after obtaining proper consent. Results: A total of 250 street children were interviewed. Out of total 250 children included in the study 162 (68.4%) were undernourished (BMI< 18.5).157 (62.8%) were suffering from nutritional anaemia. 38 (15.2%) children had various symptoms of Vitamin A deficiency.( Night blindness 8%, conjunctival xerosis 1.2%, Bitots spots 6%).A total of 62 (24.7%) children had various symptoms of group B vitamins deficiencies. Conclusion: There is an urgent need of coordination among development agents working for the rights of street children and information sharing among all stakeholders to enhance implementation strategies.